The Ethiopian Orthodox Church's tradition on the Holy Cross - Getatchew Haile, 1931- (Texts and Studies in Eastern Christianity, 2017)
The Ethiopian Orthodox Church's Tradition on the Holy Cross is a volume that combines both ancient and derived Ethiopic literature on the Cross. The work brings together all the major sources from manuscripts preserved in different monasteries and edited and translated into English. The sources include homilies by Minas bishop of Aksum, John Chrysostom, James of Sarug, as well as a number of anonymous authors, all translated from Greek during the Aksumite era. The derived literature includes works by the famous men of the pen, including the fifteenth-century Abba Giyorgis of Sägla and Emperor Zär'a Ya'ǝqob. Poetic hymns to the Cross constitute a part of the collection, one of these being glorification of the Cross by Abba Baḥrǝy, author of several important works.